Financial Attitude of Sari-Sari Store Owners in Barangay Batinguel Dumaguete City towards Microfinancing - Jaysone Christopher M. Bancoro; Benjamin S. Villagonzalo Jr; Ildefe T. Villanueva (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study investigates the borrowing and financial behavior of microbusiness owners in Barangay Batinguel, Dumaguete City, Negros Oriental, Philippines, focusing on sari-sari store owners. The research aims to determine their demographic profile, borrowing behavior, financial behavior, and the relationship between their demographic profile and financial and borrowing behavior. A descriptive method was employed, utilizing a self-made questionnaire to collect data from 19 registered sari-sari store owners selected through purposive sampling. Results revealed that the majority of respondents were aged 41 years or older, predominantly female, with family incomes of PHP 10,000 or less. Borrowing behavior varied, with most borrowing 1-2 times per year, and loan amounts ranging from PHP 3,000 to above PHP 10,000. Financial behavior assessments showed that respondents demonstrated a moderate level of financial literacy. The analysis indicated that demographic factors, such as age, sex, family income, educational attainment, years of operation, and monthly sales, influenced the financial behavior of the respondents. The study recommends increased access to financial literacy programs for microbusiness owners and the development of tailored financial support policies by financial institutions and government agencies. Future research should explore other factors affecting borrowing and financial behavior and expand the scope of the study to other regions in the Philippines.